Conflict, income shocks, and foreign policy: macro- and micro-level evidence - Langlotz, Sarah (2018)
Chapter 1: This chapter studies the effects of bilateral foreign aid on conflict escalation and deescalation. We make three major contributions. First, we combine data on civil wars with data on low level conflicts in a new ordinal measure capturing the two-sided and multifaceted nature of conflict. Second, we develop a novel empirical framework. We propose a dynamic ordered probit estimator that allows for unobserved heterogeneity and corrects for endogeneity. Third, we identify the causal effect of foreign aid on conflict by predicting bilateral aid flows based on electoral outcomes of donor countries that are exogenous to recipients. We establish that the effect of foreign aid on the various transition probabilities is heterogeneous and can be substantial. Receiving bilateral aid raises the chances of escalating from small conflict to armed conflict, but we find little evidence that aid ignites conflict in truly peaceful countries. Chapter 2: We use an excludable instrument to test the effect of bilateral foreign aid on economic growth in a sample of 96 recipient countries over the 1974-2009 period. We interact donor government fractionalization with a recipient country's probability of receiving aid. The results show that fractionalization increases donors' aid budgets, representing the over-time variation of our instrument, while the probability of receiving aid introduces variation across recipient countries. Controlling for country- and period-specific effects that capture the levels of the interacted variables, the interaction provides a powerful and excludable instrument. Making use of the instrument, our results show no significant effect of aid on growth in the overall sample. We also investigate the effect of aid on consumption, savings, and investments, and split the sample according to the quality of economic policy, democracy, and the Cold War period. With the exception of the post-Cold War period (where abundant aid reduces growth), we find no significant effect of aid on growth in any of these sub-samples. None of the other outcomes are affected by aid. Chapter 3: We combine temporal variation in international drug prices with new data on spatial variation in opium suitability to examine the effect of opium profitability on conflict in Afghanistan. District level results indicate a conflict-reducing effect over the 2002-2014 period, both in a reduced-form setting and with three different instrumental variables. We provide evidence for two main mechanisms. First, the importance of contest effects depends on the degree of violent group competition over valuable resources. By using data on the drug production process, ethnic homelands, and Taliban versus pro-government influence, we show that on average group competition for suitable districts is relatively low in Afghanistan. Second, we highlight the role of opportunity costs by showing that opium profitability positively affects household living standards, and becomes more important after a sudden rise in unemployment due to the dissolution of large armed militias after an exogenous policy change. Chapter 4: This chapter analyses how foreign military interventions relate to the internal cohesion of communities and the role of local institutions in times of conflict. I consider the case of Afghanistan where households have been exposed to conflict for decades. Given an environment where formal institutions are unstable or even lacking, the local community becomes more important. Relying on support from others in the community is thus a common strategy for households to cope with different types of shocks. At the same time, the success of security missions crucially depends on cohesion within communities as they are relevant partners in counterinsurgency and reconstruction activities. I address endogeneity by applying different estimation techniques, including a geographic regression discontinuity design. My findings suggest that households in districts where foreign military forces are present receive less help from others in their community, have less trust in community councils and participate less in those councils.